2010
DOI: 10.1158/0008-5472.can-09-2468
|View full text |Cite
|
Sign up to set email alerts
|

Novel STAT3 Phosphorylation Inhibitors Exhibit Potent Growth-Suppressive Activity in Pancreatic and Breast Cancer Cells

Abstract: The constitutive activation of signal transducer and activator of transcription 3 (STAT3) is frequently detected in most types of human cancer where it plays important roles in survival, drug resistance, angiogenesis, and other functions. Targeting constitutive STAT3 signaling is thus an attractive therapeutic approach for these cancers. We have recently developed novel small-molecule STAT3 inhibitors, known as FLLL31 and FLLL32, which are derived from curcumin (the primary bioactive compound of turmeric). The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(198 citation statements)
references
References 44 publications
6
192
0
Order By: Relevance
“…20 FLLL32 is a curcumin analog, the modification of which can better interact with binding sites of JAK2 and dimerization domain of STAT3. The treatment of FLLL32 can suppress JAK2 activity 18 but did not affect JAK2 expression or phosphorylation (Fig. 4B).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…20 FLLL32 is a curcumin analog, the modification of which can better interact with binding sites of JAK2 and dimerization domain of STAT3. The treatment of FLLL32 can suppress JAK2 activity 18 but did not affect JAK2 expression or phosphorylation (Fig. 4B).…”
Section: Discussionmentioning
confidence: 90%
“…FLLL32 is a new curcumin analog designed in our laboratory, which can specifically inhibit STAT3 in vitro and in vivo. 18 We concluded that, compared to anti-IL-6 antibody, STAT3 small-molecule inhibitors can block IL-6-induced STAT3 activation much more effectively.…”
Section: Introductionmentioning
confidence: 87%
“…This pro-inflammatory cytokine is implicated in a milieu of cancer types because of its propensity to drive the activation of the oncogenic transcription factor signal transducer and activator of transcription 3 (STAT3). By virtue of interacting with other transcription factors (e.g., NF-B), STAT3 is known to mediate crosstalk between tumor cells and inflammatory cells within the tumor microenvironment and promote the development and progression of multiple types of human cancers [12][13][14][15][16][17]. The expression of STAT3 and presence of its active form (i.e., phosphorylated form) is increased in tumor tissues from patients and this pronounced expression indicates a poor prognosis in a variety of cancers [18].…”
Section: Research Papermentioning
confidence: 99%
“…Tetrahydropyranylation of the phenoxy groups had a positive impact on the anti-androgenic activity of 4-ethoxycarbonylethylenyl curcumin. Di-tetrapyranylated-4-ethoxycarbonylethylenyl curcumin (85), which exists only in the keto-enol form, has potent anti-androgenic activity, which may be a good lead compound for further structural modifications. Based on the SAR information, five new compounds were designed and subsequently synthesized.…”
Section: Modifications Of Doublementioning
confidence: 99%
“…The compounds 101-105 were found to induce cytotoxicity against B16 melanoma cells, while compound 102 was found to inhibit tubulin polymerization. Lin et al [85] have developed signal transducer and activator of transcription-3 (STAT3) inhibitors, known as FLLL31 (106) and FLLL32 (107), which are derived by functionalization of the methylenic position in curcumin. These compounds are designed to bind selectively to Janus kinase-2 and the STAT3 Src homology-2 domain, which serve crucial role in STAT3 dimerization and signal transduction.…”
Section: Modifications Of Doublementioning
confidence: 99%